The Attentional Dependence of Emotion Cognition Is Variable with the Competing Task - Chen, Cheng; Jin, Kaibin; Li, Yehua; Yan, Hongmei (Frontiers in Behavioral Neuroscience, 2016)
The relationship between emotion and attention has fascinated researchers for decades. Many previous studies have used eye-tracking, ERP, MEG and fMRI to explore this issue but have reached different conclusions: some researchers hold that emotion cognition is an automatic process and independent of attention, while some others believed that emotion cognition is modulated by attentional resources and is a type of controlled processing. The present research aimed to investigate this controversy, and we hypothesized that the attentional dependence of emotion cognition is variable with the competing task. Eye-tracking technology and a dual-task paradigm were adopted, and subjects’ attention was manipulated to fixate at the central task to investigate whether subjects could detect the emotional faces presented in the peripheral area with a decrease or near-absence of attention. The results revealed that when the peripheral task was emotional face discrimination but the central attention-demanding task was different, subjects performed well in the peripheral task, which means that emotional information can be processed in parallel with other stimuli, and there may be a specific channel in the human brain for processing emotional information. However, when the central and peripheral tasks were both emotional face discrimination, subjects could not perform well in the peripheral task, indicating that the processing of emotional information required attentional resources and that it is a type of controlled processing. Therefore, we concluded that the attentional dependence of emotion cognition varied with the competing task.